2012
DOI: 10.1007/s00586-012-2492-8
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological survey of ossification of the ligamentum flavum in thoracic spine: CT imaging observation of 993 cases

Abstract: Objective To investigate the characteristics of epidemiological distribution of the ossification of the ligamentum flavum (OLF) in the thoracic spine including the incidence, segmental distribution, and shape. Methods Chest spiral computed tomography scans of 993 cases (male 506, female 487, mean age 60 years, range 5-102 years) who presented due to chest symptoms were analyzed with axial slices combined with sagittal slices. The conditions of OLF in the thoracic spine, including segments, thickness, location,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
108
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(114 citation statements)
references
References 19 publications
3
108
3
Order By: Relevance
“…15,18,34,54,55 In our study, we also found similar results. In addition, it has been reported Clinical characteristics and surgical outcome of TM caused by OLF Z Li et al that the location of OLF is less vulnerable in mobile segments such as the cervical and lumbar vertebra than in the thoracic vertebrae.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…15,18,34,54,55 In our study, we also found similar results. In addition, it has been reported Clinical characteristics and surgical outcome of TM caused by OLF Z Li et al that the location of OLF is less vulnerable in mobile segments such as the cervical and lumbar vertebra than in the thoracic vertebrae.…”
Section: Discussionsupporting
confidence: 89%
“…Analysis of previously published epidemiological data revealed that the mean age of thoracic OLF patients ranged from 50 to 60 years and most required surgical treatment. 17,18,21 Another large-scale epidemiological study on OLF in patients who presented with chest symptoms and underwent multidetector CT examination showed that the prevalence rate of OLF was much higher, at 63.9%, than in previous reports. 18 The process of OLF occurred earlier than was previously thought and was even found in 10-19-year-old individuals.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations